Romania - Functional Review : Transport Sector - World Bank (Washington, DC, 2013)
This report describes the results of the Functional Review of the transport sector in Romania. During its early transition years, Romania implemented radical structural reforms in the institutions of the transport sector, but over the last decade there has been concern that these changes have not led to tangible improvements in transport policy administration nor in the efficiency and effectiveness of the main delivery institutions in the railway and road sectors. The Review has tried to discern the main reasons for these shortcomings and to identify remedial actions. It focuses on three main challenges: the administration of the transport sector as a whole; the corporate governance of state-owned road and railway companies; and the priorities for the companies themselves. Attention is also given to budgeting issues and opportunities for greater private sector participation.